Philo of Alexandria: On the Life of Abraham : Introduction, Translation, and Commentary - Birnbaum, Ellen, (Philo of Alexandria Commentary Series ;, 2020)
On the Life of Abraham displays Philo's philosophical, exegetical, and literary genius at its best. Philo begins by introducing the biblical figures Enos, Enoch, Noah, Abraham, Isaac, and Jacob as unwritten laws. Then, interweaving literal, ethical, and allegorical interpretations, Philo presents the life and achievements of Abraham, founder of the Jewish nation, in the form of a Greco-Roman bios, or biography. Ellen Birnbaum and John Dillon explain why and how this work is important within the context of Philo's own oeuvre, early Jewish and Christian exegesis, and ancient philosophy. They also offer a new English translation and detailed analyses, in which they elucidate the meaning of Philo's thought, including his perplexing notion that Israel's ancestors were laws in themselves.